Village Baseline Study – Site Analysis Report for My Loi, Ky Anh district, Ha Tinh province – Viet Nam - Hai, Le Van; Duong, Minh Tuan; Hieu, Do Trong; Hoan, Le Khai; Lien, Phan Huong; Simelton, Elisabeth; Ferrer, Alice J.; Tan Yen, Bui (2014)
Data collection for the Village Baseline Study (VBS) of My Loi village in the CCAFS benchmark site of central Viet Nam took place on 17- 19 October 2014. Focus group discussions were conducted separately for 45 men and 45 women villagers.. The VBS had three main topics: map of (1) community resources, (2) organizational landscapes, and (3) information networks. A seminar was held in December 2014 to seek participants’ feedback. My Loi village has experienced multiple extreme weather events (temperature and water stresses, storms and typhoons) throughout the years. The main constraints for agricultural development and livelihoods are limited water resources and poor conditions of irrigation systems, which are challenges to improving the agricultural production situation. Moreover, sand and rock mining have caused water pollution, erosion on riverbanks and loss of farmland area. Another constraint is marketing, as villagers are not aware of any organization involved in finding outlets for agricultural products. The potentials for developing innovative climate-smart solutions in the village are several: farmers have experiences and are interested in trying new varieties and adjusting farming calendars to improve the situation. Livestock expansion and agroforests/reforestation hold opportunities for improving household incomes. Furthermore, at least half of the organisations identified in the region are working to address food security issues.